ANALISA PERFORMA HEAT EXCHANGER DENGAN PENAMBAHAN VORTEX GENERATOR TIPE DELTA WING DAN DELTA WINGLET TAPE INSERT GUNA MENGATASI ICING PADA KARBURATOR PISTON ENGINE - A. R. Ramadhan; Gaguk Marausna; Farid Jayadi (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2023)
The simple simulation tool of the heat exchanger has a limitation, that is, when the heat transfer process cannot be analyzed directly, and the flow motion cannot be observed. Therefore it can be solved by the CFD method. The purpose of this study is to provide observable visual images. In this simulation, it uses a tube given a vortex generator with delta variations adding angles, each of which is given a constant inlet velocity, inlet temperature, and heatflux input values. Each angle is given a value of 200, 400, 600. This study aims to obtain a vortex generator with the best angular variation. From the research that has been carried out, it shows that the addition of delta provides a difference in the results of each specimen tested, the addition of a delta winglet with the addition of an angle of 400 is produced to have the best heat transfer coefficient, it is shown at a low temperature difference (ΔT). Analysis of the results of a low temperature difference (ΔT) means that the specimen performed good heat transfer performance.